2019
DOI: 10.1111/1749-4877.12396
|View full text |Cite
|
Sign up to set email alerts
|

Population dynamics of three lizard species from the genus Sceloporus: short‐term changes in demographic parameters

Abstract: Most demographic studies focus on numerical changes that occur within populations across years. However, typically studies at an interannual scale do not provide information on the particular times of the year (particular months or seasons) when rates of survival, recruitment, or migration increase or decrease due to physiological, behavioral or ecological processes. These monthly or seasonal changes in demographic parameters may lead to substantial variations in population abundance. In this study, we collect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 78 publications
(78 reference statements)
0
3
0
Order By: Relevance
“…In tropical forests, they occupy a similar trophic level to that of litter‐dwelling amphibians (Inger, 1980; Vitt & Caldwell, 1994). Taking into account the great diversity and abundance of lizards, especially in desert, semiarid and insular communities, they can have a major impact on ecosystem resources (Morton & James, 1988; Buckley & Jetz, 2007; Vargas‐García et al ., 2019). Field experiments revealed that lizards can substantially affect the density and composition of soil invertebrate communities, mainly by reducing the abundance of their target prey groups (Spiller & Schoener, 1988; González‐Suárez et al ., 2011).…”
Section: Synopsis Of Feeding Habitsmentioning
confidence: 99%
“…In tropical forests, they occupy a similar trophic level to that of litter‐dwelling amphibians (Inger, 1980; Vitt & Caldwell, 1994). Taking into account the great diversity and abundance of lizards, especially in desert, semiarid and insular communities, they can have a major impact on ecosystem resources (Morton & James, 1988; Buckley & Jetz, 2007; Vargas‐García et al ., 2019). Field experiments revealed that lizards can substantially affect the density and composition of soil invertebrate communities, mainly by reducing the abundance of their target prey groups (Spiller & Schoener, 1988; González‐Suárez et al ., 2011).…”
Section: Synopsis Of Feeding Habitsmentioning
confidence: 99%
“…One is that of Vargas‐García et al. (2019), who based on demographic analyses suggested that S. grammicus migration rate did not vary throughout the seasons of the year, although they could not confirm long‐distance movements. Likewise, Sites et al.…”
Section: Discussionmentioning
confidence: 96%
“…Although S. grammicus has been studied on a wide range of topics, notably its dispersal or migration has been little examined, with only a few examples. One is that of Vargas-García et al (2019), who based on demographic analyses suggested that S. grammicus migration rate did not vary throughout the seasons of the year, although they could not confirm long-distance movements. Likewise, Sites et al (1995) report that males usually move greater distances (154 m) compared to females (77 m) and that although long-distance movements are possible, they are rare.…”
Section: Environmental and Anthropogenic Factors Mediating Functional...mentioning
confidence: 96%
“…In our study species, several individuals of all stage classes were not detected at least once during our field surveys (30 out of 154 seedlings [19%], 9 out of 44 juveniles [20%], 4 out of 28 adults 1 [14%], and 2 out of 29 adults 2 [7%]), which justified the use of demographic models that explicitly estimated stage-specific detection probabilities. Multistate models accounted for this imperfect detectability and permitted the calculation of demographic rates on intra-annual scales (Brownie et al 1993;Nichols and Kendall 1995;Stanley and Burnham 1998;Vargas-García et al 2019). In the constructed models:…”
Section: Multistate Models Analysismentioning
confidence: 99%
“…For instance, seedlings have a lower probability of being detected during field surveys compared with adult plants (Kéry and Greg 2003). In addition, most of these capture-recapture methods, including multistate models, can be applied at an intra-annual scale (Vargas-García et al 2019;White et al 2006). Such an application allows examining the effects of environmental factors that vary within years (e.g., the rainy season) on the life history and demographic rates of species of interest (Moustakas and Evans 2015).…”
Section: Introductionmentioning
confidence: 99%